PD1hi cells associate with clusters of proliferating B-cells in marginal zone lymphoma - Katherine Wickenden; Nadia Nawaz; Sami Mamand; Deevia Kotecha; Amy L. Wilson; Simon D. Wagner; Matthew J. Ahearne (BMC, 2018)
Abstract Background Abnormally sustained immune reactions drive B-cell proliferation in some cases of marginal zone lymphoma but the CD4+ T-cell subsets, which are likely to contribute to the B-cell responses in the tumour microenvironment, are not well characterised and neither has the spatial distribution of the different subsets in involved lymph nodes been investigated. Methods Employing a workflow of multiplex semi-automated immunohistochemistry combined with image processing we investigated association between infiltrating T-cells and proliferating lymphoma B-cells. Results Both total numbers of activating follicular helper (Tfh) cells (defined by high expression of PD1) and suppressive regulatory (Treg) T-cells (defined by FOXP3+ expression) and the Tfh:Treg ratio, assessed over relatively large areas of tissue, varied among cases of marginal zone lymphoma. We determined spatial distribution and demonstrated that PD1hi cells showed significantly more clustering than did FOXP3+. To investigate the association of infiltrating T-cells with lymphoma B-cells we employed Pearson correlation and Morisita-Horn index, statistical measures of interaction. We demonstrated that PD1hi cells were associated with proliferating B-cells and confirmed this by nearest neighbour analysis. Conclusions The unexpected architectural complexity of T-cell infiltration in marginal zone lymphoma, revealed in this study, further supports a key role for Tfh cells in driving proliferation of lymphoma B-cells. We demonstrate the feasibility of digital analysis of spatial architecture of T-cells within marginal zone lymphoma and future studies will be needed to determine the clinical importance of these observations.